Cytokinetic study of uninfected agarwood branch ethanolic extract on breast cancer cells - Abbas, Phirdaous; Hashim, Yumi Zuhanis Has-Yun; Amid, Azura (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Breast cancer is the most common malignancy in women with more than 500,000 global death toll annually. Evidences from ethnopharmaceutical practices showed that Aquilaria spp. from Thymelaeceae family has been used traditionally as treatment of a wide range of disorders. However, scientific evidences are still lacking in order to support the traditional applications on cancer disease. This study was aimed to investigate the cytotoxic kinetics of uninfected agarwood branch ethanolic extract from Aquilaria subintegra against MCF-7 breast cancer cell line that may help understand the effect and provide baseline towards development of agarwood-based therapeutics. Screening assays conducted revealed that the extract may possess anti-attachment and cytotoxic effects against MCF-7 breast cancer cells with a significant inhibition concentration (IC50) of 8 μg/ml when tested using sulforhodamine B (SRB) assay. Extract was subjected to a series of kinetic study in order to investigate the growth rate, death rate, doubling time and death time of MCF-7 between the treated and control groups. Experiments were conducted in triplicates and results obtained showed that the extract reduced the cell generation number of MCF-7 from 3.52 to 1.22 and the growth rate from 0.0421 h-1 to 0.0158 h-1. Doubling time of MCF-7 cells was extended from 16.4 hours to 43.8 hours. The death rate was increased from 0.0058 h-1 to 0.0563 h-1. Closer observation on the population density images revealed that the extract-treated MCF-7 cells showed irregular appearance with blebs, volume reduction, cell shrinking and loss of cell-cell contact. Data collected made it possible to develop an early model of cancer dose treatment using the first order linear equation as a function of time that can be used to estimate cell size or volume of cancer, speed of growth and possibility of successful dosage/treatments using data from biopsy procedure. These findings suggested that agarwood uninfected branch ethanolic extract affect the cytokinetics of MCF-7 cells which warrants further research and focus in validating the hypothesis and elucidating the effects against cancer.